2009
DOI: 10.1097/jto.0b013e3181990c46
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Cardiac Perfusion Abnormalities After Chemoradiotherapy in Patients with Lung Cancer

Abstract: CRT/RT to centrally located lung tumors tends to cause anterior/septal MPI defects. Abnormal MPI segments in the CRT/RT group have received significantly higher radiation than normal segments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 26 publications
3
3
0
Order By: Relevance
“…These factors included smoking (SMK), atrial fibrillation (AFib), COPD, and obesity. These findings substantiated what has been reported previously for lung cancer, 53,54,57,67 and they further provide supportive evidence for the inflammation hypothesis linking CVD and cancers. 60 However, our multivariate analyses did not find any additional risk factor in relation to LC except for hypertension among black patients (OR= 1.37, CI: 1.16–1.62), and cholesterol among whites (OR=1.16, CI: .06–1.26).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These factors included smoking (SMK), atrial fibrillation (AFib), COPD, and obesity. These findings substantiated what has been reported previously for lung cancer, 53,54,57,67 and they further provide supportive evidence for the inflammation hypothesis linking CVD and cancers. 60 However, our multivariate analyses did not find any additional risk factor in relation to LC except for hypertension among black patients (OR= 1.37, CI: 1.16–1.62), and cholesterol among whites (OR=1.16, CI: .06–1.26).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, CHD did not show a relationship with LC in our analyses (Table 2, col. 13). However, a relationship between CHD and AFib could develop (in 14 months post-treatment) due to cancer treatment modalities such as radiation therapy, chemo-therapy or surgery 54,76 AFib among cancer patients may also develop due to frequent use of aspirin which reportedly increases AFib by 12%. 77 Hence, the presence of AFib (which existed in 34% of our CHD patients) may occur from the NSAID use.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this study has also confirmed our previously identified specific patterns of MPI abnormality of inferior wall ischemia noted in distal esophageal cancer patients [20] and anterior/septal ischemia pattern in centrally located lung cancer patients [21]. This inferior ischemia in esophageal cancer patients is usually due to the proximity of the more common distal esophageal tumors to the heart resulting in inclusion of the inferior wall of the left ventricle in the RT field.…”
Section: Discussionsupporting
confidence: 89%
“…3 Another study demonstrated that with lung cancer, chemotherapy and radiation to centrally located lung tumors cause defects in cardiac perfusion anteriorly, corresponding to those regions that have received higher levels of radiation. 4 Similar conclusions about long-term toxicity have been made with respect to pulmonary side effects such as late radiation fibrosis. 5 It is in this context that the advancement of radiation techniques could have a large impact on reducing serious morbidity, and that this benefit will continue to be witnessed for many years to come.…”
supporting
confidence: 52%